2022
DOI: 10.3390/cells11203188
|View full text |Cite
|
Sign up to set email alerts
|

PFN1 Inhibits Myogenesis of Bovine Myoblast Cells via Cdc42-PAK/JNK

Abstract: Myoblast differentiation is essential for the formation of skeletal muscle myofibers. Profilin1 (Pfn1) has been identified as an actin-associated protein, and has been shown to be critically important to cellular function. Our previous study found that PFN1 may inhibit the differentiation of bovine skeletal muscle satellite cells, but the underlying mechanism is not known. Here, we confirmed that PFN1 negatively regulated the myogenic differentiation of bovine skeletal muscle satellite cells. Immunoprecipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Among MRF, muscle cell proliferation is mainly controlled by Myf5 and MyoD, while differentiation is primarily controlled by MRF4 and MyoG in muscle development ( Song et al., 2015 ). There is a high level of expression of MYHC in differentiated myoblasts, which promotes cell fusion and leads to the formation of myotubes ( Zi et al., 2022 ). Our findings demonstrated that AFB1 downregulated MyoG , MyoD , MRF4 , Myf5 , and MYHC mRNA expression in grass carp muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Among MRF, muscle cell proliferation is mainly controlled by Myf5 and MyoD, while differentiation is primarily controlled by MRF4 and MyoG in muscle development ( Song et al., 2015 ). There is a high level of expression of MYHC in differentiated myoblasts, which promotes cell fusion and leads to the formation of myotubes ( Zi et al., 2022 ). Our findings demonstrated that AFB1 downregulated MyoG , MyoD , MRF4 , Myf5 , and MYHC mRNA expression in grass carp muscle.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA and Rac1 have been shown to positively regulate myogenic differentiation through serum response factor (SRF) and β-catenin/TGF, which activate the expression of MyoD, thereby promoting myogenesis [79,80]. Moreover, the interaction of PFN1 with Cdc42, a GTPase protein, has been shown to stimulate PAK/JNK signaling pathways, altering cytoskeletal dynamics and inhibiting myogenic differentiation [81]. In a study by Kooij et al, overexpression of PFN2a in Drosophila resulted in reduced climbing ability of flight muscles, diminished flight capability, and elongated thin filaments [82].…”
Section: Profilin (Pfn)mentioning
confidence: 99%
“…Fu et al [27] have reported that Egl nine homolog 3 (EGLN3, also known as PHD3) regulates skeletal muscle differentiation by modulating the stability of the myogenin protein. Cell division control protein 42 homolog (Cdc42) has been identified as a negative regulator of the differentiation of skeletal muscle cells [28]. Similarly, the homeobox protein Hox-A11 has a significant inhibitory effect on myogenesis during muscle differentiation [29].…”
Section: Introductionmentioning
confidence: 99%